Analysis of Translation Methods for Artistic Translation - Zаfаrjon, Djаlolov (Journal of Higher Education and Academic Advancement, 2024)
The main feature of artistic translation comes from the artistic function of the language. Language becomes an aesthetic phenomenon, an art fact in a work of art. The language of a literary work is the element of "artistic reality" in ethics. In translation, it is this figurative process of transferring the artistic meaning in the traditional language to the figurative expressive ground of another language, re-expressing the image with the image takes place. Therefore, the translator perceives anew the process of artistic thinking of events in the work. In this article, opinions and considerations will be made about the analysis of methods for artistic translation.